Preparation of Salted-pressed Psenes indicus and its Storage Characteristics - Chakraborti, R.; Gupta, S.S; Panduranga Rao, C.C. (Fishery Technology, 2025)
This paper describes a process for the preparation of salted and pressed Psenes indicus and its storage characteristics. Dressed Psenes indicus immersed in saturated brine for 7 days, were pressed under pressure of 0.048 to 0.08 kg/cmz. The salted and pressed fish packed in 70 p. nylon/surlyn bag under vacuum was acceptable for 120135 days, while those packed in 200 gauge polythene bag without vacuum was acceptable for 45-60 days at ambient temperature. 0.1 % propionic acid treated salted and pressed Psenes indicus had 15 days longer storage life than untreated one.